Deep ocean temperatures in the eastern equatorial Pacific Ocean at the Eocene-Oligocene Transition - Victoria E Taylor; Paul A Wilson; Steven M Bohaty; Anna Nele Meckler (PANGAEA, 2023)
This dataset contains clumped isotope, and stable carbon and oxygen isotope data from benthic foraminifera from IODP Expedition 320 Sites U1334 and U1333, and ODP Site 1218, in the eastern equatorial Pacific Ocean. The clumped isotope data were used to reconstruct deep ocean temperatures from ~35 Ma to ~33 Ma, across the Eocene-Oligocene Transition. Data in this dataset are provided as averaged stable isotope and temperature data, whereby each individual temperature represents the average of a minimum of 30 measurements of aliquots of monospecific benthic foraminifera sourced from multiple (n = 11-34) closely spaced samples.